224k views
1 vote
Please answer thiss!!!!

Please answer thiss!!!!-example-1
User NsL
by
5.4k points

1 Answer

2 votes

Answers:

a = 1/3

b = -6

c = 7

======================================================

Step-by-step explanation:

The terms of the given expression rearrange to
(1)/(3)x^2 - 6x+7 which is now in standard form (the exponents decrease when moving from left to right).

We can see that

a = 1/3

b = -6

c = 7

after matching that with the ax^2+bx+c form.

User Chris Finley
by
4.1k points